Synthesis, heat transport mechanisms and thermophysical properties of nanofluids: A critical overview. (May 2021) - Awais, Muhammad; Bhuiyan, Arafat A.; Salehin, Sayedus; Ehsan, Mohammad Monjurul; Khan, Basit; Rahman, Md. Hamidur
Highlights: Synthesis, characterization and stability of nanofluid is elaborated. Thermophysical properties and their dependency on crucial factors are elucidated. Measurement techniques of transport properties are discussed. Mathematical models of thermophysical properties are reviewed. Abstract: Unique thermophysical properties of nanofluids set them apart from conventional basefluids; nanofluids impart substantial role in enhancing heat transfer performance since they have the advantage of exhibiting superior thermal conductivity. Due to their numerous applications in various industrial and engineering sectors, researchers have been putting significant efforts to tailor the transport properties of nanofluids and demonstrate the influence of various prominent factors on thermal performance of nanofluids while finding out their optimal values. Upon briefly providing an overview of the preparation methods, and stability of nanofluids, this study provides a critical review of the crucial mechanisms e.g. Brownian motion, thermophoresis, osmophoresis, electrophoresis, and aggregation kinetics responsible for thermal conductivity variation in nanofluids. The impact of few key parameters (size, shape and concentration of nanoparticles) on thermal conductivity has been comprehensively discussed. Crucial measurement techniques of thermophysical properties of nanofluids coupled with their mathematical models are extensively reviewed. This study shall provide greater insight for researchers and designers to incorporate the use of adequate nanofluids while properly comprehending the physical phenomenon and the nature of their transport properties.